Cyclic nucleotide-independent protein kinases from ribosomes and phosphorylation of a single 40S ribosomal subunit protein in zoospores of Blastocladiella emersonii. - Bonato, M C (1983)
Cyclic nucleotide-independent protein kinase (EC 2.7.1.37) activity was found in the nuclear cap organelle, within which ribosomes of zoospores of Blastocladiella emersonii are sequestered. Two protein kinase activities were resolved from the high-salt wash fraction of zoospore ribosomes by selective adsorption to DEAE-cellulose. Both enzymes phosphorylated in vitro a 32,000 Mr protein of the 40S ribosomal subunit. Phosphorylation of this ribosomal protein, which exhibits electrophoretic properties similar to those of mammalian ribosomal protein S6, was also observed in vivo in 32P-labeled zoospores.